Characterization and prospective of Chilika buffalo – a unique germplasm of Eastern India - S.K.Dash; B.P.Sethi; P.C.Ray; B.Prakash (Journal of Livestock Biodiversity, 2025)
This study aims at understanding the buffalo production system and production constraints and identifying breeding goals of breeders in Chilika buffalo areas in eastern India as the first step towards developing a sustainable breed improvement programme. Detailed survey on evaluation and characterization of Chilika buffalo was carried out by collecting information on herd structure, prevailing management practices, body conformation, production and reproduction performance in its native tract. Average body weight, height at withers, body length, heart girth, punch girth, tail length and horn length in males were 352.56±2.48 kg, 125.87±0.78, 122.72±0.26, 172.63±0.33, 168.36±0.55, 72.32±0.12 and 48.32±0.24 cm, respectively. The corresponding figures in females were 341.38±1.23 kg, 123.64±0.65, 120.58±0.12, 171.42±0.13, 168.42±0.21, and 72.16±0.08 and 50.76±0.12 cm, respectively. Highest lactation milk yield was recorded as 514.54 litres in a lactation length of 262 days in 4th parity with average fat content of 8.68 %. Cytogenetic profile of Chilika buffalo is typical riverine type (2n=50, XX or 50, XY).